ChemInform Abstract: Copper‐Powder‐Catalyzed Synthesis of Pyrimidines from β‐Bromo α, β‐Unsaturated Ketones and Amidine Hydrochlorides. Issue 38 (3rd September 2015) - Jiao, Yang; Ho, Son Long; Cho, Chan Sik
Abstract The reaction provides a new method for synthesizing pyrimidines starting from readily available ketones and amidine hydrochloride.